The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2196/13776
|View full text |Cite
|
Sign up to set email alerts
|

Usability, Acceptability, Feasibility, and Effectiveness of a Gamified Mobile Health Intervention (Triumf) for Pediatric Patients: Qualitative Study

Abstract: BackgroundMental disorders are notably prevalent in children with chronic illnesses, whereas a lack of access to psychological support might lead to potential mental health problems or disruptions in treatment. Digitally delivered psychological interventions have shown promising results as a supportive treatment measure for improving health outcomes during chronic illness.ObjectiveThis study aimed to evaluate the usability, acceptability, and feasibility of providing psychological and treatment support in a cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 48 publications
0
32
0
1
Order By: Relevance
“…It is documented that promoting children’s health with active digital games seems quite promising even among other fields of health, such as physical activity [ 56 ]. Self-management behaviors of young people with chronic diseases [ 57 ] or support of pediatric cancer patients, where a statistically significant decrease in general health problems and a trend toward a decrease in depression and anxiety symptoms were observed after implementation of a mobile health game [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is documented that promoting children’s health with active digital games seems quite promising even among other fields of health, such as physical activity [ 56 ]. Self-management behaviors of young people with chronic diseases [ 57 ] or support of pediatric cancer patients, where a statistically significant decrease in general health problems and a trend toward a decrease in depression and anxiety symptoms were observed after implementation of a mobile health game [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The insertion of serious games in both hospital and domestic contexts can lead to immersion in the experienced issue, providing an opportunity to discuss the conditions for health promotion, in addition to promoting reflection on unhealthy habits or inefficient care [ 14 , 26 , 28 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies observed benefits through telemedicine strategies in young adults, especially, if face‐to‐face videoconferencing is used or gamification techniques were deployed [66,70]. Another study addressed caretakers of young transplant recipients and described an improved post‐transplant care by an app supported discharge program enabling better communication [67].…”
Section: Mobile Applications (Apps)mentioning
confidence: 99%